2009
DOI: 10.1007/s10096-009-0807-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of procalcitonin in acutely hospitalized elderly patients

Abstract: The aim of this study was to evaluate procalcitonin as an adjunct to diagnose bacterial infections in older patients. One hundred seventy-two patients admitted to an acute-care geriatric unit during a 6-month period were prospectively included, 39 of them with an invasive bacterial infection. The best cut-off value to rule in a bacterial infection was 0.51 microg/l with sensitivity 64% and specificity 94%. The best cut-off value to rule out a bacterial infection was 0.08 microg/l with sensitivity 97% and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…Bacterial infection was diagnosed in 134 patients [overall prevalence, 15.83% (range 9–23%)] (Table ). PCT tests were used in all four studies , and CRP and leucocyte count tests were evaluated in three of them .…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial infection was diagnosed in 134 patients [overall prevalence, 15.83% (range 9–23%)] (Table ). PCT tests were used in all four studies , and CRP and leucocyte count tests were evaluated in three of them .…”
Section: Resultsmentioning
confidence: 99%
“…27 Among the elderly and immunocompromised patients, however, the classic signs of sepsis may be missing because of decreased inflammatory responses in such patients. 30 In addition, it has been shown that serum PCT levels correlate positively with the severity of inflammatory responses to infections. 31 This can explain why serum procalcitonin is a more reliDiagnostic anD prognostic performances of serum procalcitonin in patients with blooDstream infections: a parallel, case-control stuDy comprising aDults anD elDerly rev assoc Med Bras 2017; 63(6):521-526 525 able indicator of BSIs under 65 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of PCT in differentiating bacterial pneumonia from other acute illnesses in the real world is controversial. 99,100 In addition, the role of PCT in elderly persons is unclear, because this population group is usually excluded from clinical studies. A recent retrospective study in Italy evaluated the role of CRP in elderly patients who presented to the emergency department with respiratory symptoms and were discharged with or without a final diagnosis of pneumonia.…”
Section: Laboratory Evaluationmentioning
confidence: 99%